A borderline personality assessment for adolescents: Validity and reliability of the Chinese languages borderline personality features scale (short form version) for adolescents/children - Zhuo, Chuanjun; Chen, Guangdong; Lin, Chongguang; Jia, Feng; Yang, Lei; Zhang, Qiuyu; Chen, Jiayue; Tian, Hongjun; Jiang, Deguo (Frontiers in Psychiatry, 2022)
Abstract Background: Borderline personality disorder (BPD) is characterized by behavioral patterns that promote suffering in many adolescents and their guardians. Currently, early diagnosis of BPD mainly depends on the effective assessment of pathological personality traits (i.e., borderline personality features) and using the indicated scales. The Borderline Personality Features Scale for Children-Short Form (BPFSC-SF) is widely used and the introduction of a Chinese version of the BPFSC-SF, can improve the diagnosis and prognosis of Chinese patients with BPD. Objective: The aim of the present study was to assess the validity and reliability of the Chinese version of the BPFSC-SF. Method: 120 adolescents with BPD were enrolled in the present study and completed the BPFSC-SF and the Personality Belief Questionnaire-Short Form (PBQ-SF) assessments. Confirmatory factor analysis (CFA) was used to test assessment validity. Test-retest correlations and the Cronbach’s α coefficients were used to determine reliability. Results: CFA analysis identified primary factors of BPFSC, with each item ranging from 0.597~0.899. The Spearman rank correlation coefficient was 0.877 between CL-BFSFC-SF and the state versus trait loneliness scale. The Cronbach’s α of the scale was 0.854 in the clinical group. The test-retest reliability correlation coefficient (interclass correlation coefficients .ICC) was 0.937. Conclusion: The Chinese version of BPFSC-SF is a valid and reliable tool for adolescent Chinese patients with BPD.